Modelo de Flat Tax. Una alternativa para la formalidad en Colombia. Año 2023 (2023)
This paper aims to provide valuable information regarding the feasibility of a Flat tax model of uniform type, supported on a statistical basis that has been tested in different countries of the world with a great scope and liability; this of course considered under certain particularities of the labor market and the Colombian standard.